Mid-Liver Stage Arrest of Plasmodium falciparum Schizonts in Primary Porcine Hepatocytes - van der Boor, Saskia C.; van Gemert, Geert-Jan; Hanssen, Alex E. J.; van Waardenburg, Youri M.; McCall, Matthew B. B.; Bousema, Teun; de Wilt, Johannes H. W.; Sauerwein, Robert W.; Yang, Annie S. P. (Frontiers in Cellular and Infection Microbiology, 2022)
During co-evolution Plasmodium parasites and vertebrates went through a process of selection resulting in defined and preferred parasite-host combinations. As such, Plasmodium falciparum (Pf) sporozoites can infect human hepatocytes while seemingly incompatible with host cellular machinery of other species. The compatibility between parasite invasion ligands and their respective human hepatocyte receptors plays a key role in Pf host selectivity. However, it is unclear whether the ability of Pf sporozoites to mature in cross-species infection also plays a role in host tropism. Here we used fresh hepatocytes isolated from porcine livers to study permissiveness to Pf sporozoite invasion and development. We monitored intra-hepatic development via immunofluorescence using anti-HSP70, MSP1, EXP1, and EXP2 antibodies. Our data shows that Pf sporozoites can invade non-human hepatocytes and undergo partial maturation with a significant decrease in schizont numbers between day three and day five. A possible explanation is that Pf sporozoites fail to form a parasitophorous vacuolar membrane (PVM) during invasion. Indeed, the observed aberrant EXP1 and EXP2 staining supports the presence of an atypical PVM. Functions of the PVM include the transport of nutrients, export of waste, and offering a protective barrier against intracellular host effectors. Therefore, an atypical PVM likely results in deficiencies that may detrimentally impact parasite development at multiple levels. In summary, despite successful invasion of porcine hepatocytes, Pf development arrests at mid-stage, possibly due to an inability to mobilize critical nutrients across the PVM. These findings underscore the potential of a porcine liver model for understanding the importance of host factors required for Pf mid-liver stage development.